Legal Regulation of Taxation in The Swiss Confederation - Patsurkivskyy, Petro; Havrylyuk, Ruslana (European Journal of Law and Public Administration, 2018)
The article considers the Swiss model of fiscal municipalization from the ideological and methodological positions of the anthroposociocultural approach. Such components of this approach as historical and genetic methods together with the method of system-structural analysis were applied especially thoroughly and consistently. By means of them it was found that the Swiss model of fiscal decentralization is an attributive part of the construction of public power in Switzerland – municipalization from bottom to top. Special attention is drawn to defining the basic legal features of the Swiss model of fiscal municipalization. It is argued that subsidiarity does not paradigmatically coincide with decentralization: the principle of subsidiarity postulates the sovereignty of the basic territorial collectives and considers the possible conditions for its limitation for general social needs and values. On the contrary, the principle of decentralization has the national level of governance as the starting point and considers the conditions of delegation of certain tasks and competences by the state to the lower levels of public power hierarchy in the principal frames of state sovereignty. Specificity of the principle of subsidiarity in Switzerland is that cantons play dual role from the standpoint of administrative federalism. On the one hand, they are the bearers of sovereignty of public power, including taxation. On the other hand, they are the sole bearers of administrative authority and are obliged to serve national interests, that is, the needs of the entire Swiss Confederation. Paradox is that this service function of the cantons gives them considerable benefits in the inevitable opposition to the Union state, when it comes to provision of services of the entire fiscal system and the entire system of public finance.
Keywords: Swiss fiscal municipalization; subsidiarity; sovereignty of the basic territorial collectives; Swiss instrumental state